Formation and development of North Caucasus oil industry (to the 130th anniversary of Grozny oil industry) - N. A. Kasyanova (Известия высших учебных заведений: Геология и разведка, 2024)
Background. The author presents an analysis of the emergence and development of the oil industry in the Kuban and Terek (Grozny) regions in the North Caucasus during 19th—21st centuries, paying particular attention to the Grozny oil industry on the occasion of its 130th anniversary. The process of developing the North Caucasus oil industry is divided into periods depending on the governmental and administration system at different stages of Russian history (Royal Russia, USSR, Russian Federation). As a result, there main stages are defined: 1st stage (Royal Russia for the period of the 19th — early 20th centuries); 2nd stage (USSR); and 3rd stage (Russian Federation). The most important historical events in the course of evolution of the Kuban and Grozny oil industry are given in chronological order. The role of public administration in different historical periods, including revolutionary and war years, economic crisis, and wartime devastation, is shown. The invaluable contribution of Grozny engineers, scientists, and workers of the oil production, oil refining and petrochemical industries to the development of the domestic and world oil industry is demonstrated.Aim. To analyze the history of formation and development of the North Caucasus oil industry taking into account the role of public administration.Materials and methods. A large amount of information on Russian history and the history the North Caucasus oil industry was analyzed.Results. The process of developing the North Caucasus oil industry is divided into periods depending on the governmental and administration system at different stages of Russian history.Conclusion. To identify the main factors influencing the development of the North Caucasus oil industry, i.e., technological progress and public administration. The latter played a fundamental role in the development of the oil industry in the Soviet Union and the Russian Federation.